2023
DOI: 10.14202/vetworld.2023.2382-2388
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of canine ear diseases in Northwest China: Analysis of data on 221 dogs from 2012 to 2016

J-P Li,
L-Y Li,
F-L T
et al.

Abstract: Background and Aim: Ear disease is relatively important in veterinary medicine as it significantly affects the quality of life of pets. Two hundred and twenty-one cases of canine ear diseases were collected and collated at the Xi'an Teaching Hospital of Northwest A&F University from 2012 to 2016. An epidemiological analysis was conducted to evaluate the prevalence and causes of various ear diseases in various breeds of dogs in Xi'an. Materials and Methods: Data were collected and statistically analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, similar isolation rates have been described when directly analyzing suspect otitis samples. For example, Tesin et al [ 1 ] observed a detection rate of 88.3% for bacteria and yeast from 60 ear swabs, similarly to Li et al [ 26 ], who found an 86.4% prevalence of otitis externa.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, similar isolation rates have been described when directly analyzing suspect otitis samples. For example, Tesin et al [ 1 ] observed a detection rate of 88.3% for bacteria and yeast from 60 ear swabs, similarly to Li et al [ 26 ], who found an 86.4% prevalence of otitis externa.…”
Section: Discussionmentioning
confidence: 84%
“…Other authors have found relatively similar percentages of ear disease cases when analyzing diagnostic results from large diagnostic facilities. For example, Li et al [ 26 ], observed 1% of samples associated with ear disease in sample set of 20,404 outpatient records. Although the total number of samples submitted for ear disease diagnosis were low overall, the dataset evaluated is representative of the local dog population based on statistical sample size calculation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%